Nanomaterials: Properties and Applications in Structural Engineering - Doncheva, Elisaveta; Djokikj, Jelena (SCIENTICIC TECHNICAL UNION OF MECHANICAL ENGINEERING INDUSTRY 4.0, 2022)
Nanotechnology has grown in popularity due to the enormous potential for producing materials and products with diverse properties, allowing significant advancement of existing technology and the development of new innovative technologies. Nanomaterials behave differently at the nanoscale than their conventional counterparts, opening exciting new possibilities in a wide range of construction applications. Nonetheless, the lack of information on nanomaterials' suitability, high costs, and health risks limits their use in construction and structural engineering. As a result, research must be conducted to provide accurate information and facts about the properties and performance of nanomaterials under various load conditions, as well as information on the advantages of using nanomaterials over other construction materials. This paper provides information on nanomaterial properties and how they affect structural materials' microstructure and mechanical properties. It also demonstrates the benefits of using nanotechnology and suggests new possibilities.
Keywords: nanomaterials; nanoparticles; properties; construction; coating